2014
DOI: 10.1016/j.metabol.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dairy foods, diabetes, and metabolic health: Potential mechanisms and future directions

Abstract: Epidemiological evidence supports an inverse relationship between adequate intake of dairy foods and susceptibility to type 2 diabetes (T2D). The biological mechanisms responsible for this association remain to be established. This review provides a current perspective on proposed mechanisms that may underlie these effects, and highlights how randomized clinical trials can be applied to investigate these relationships. Results from epidemiological studies generally support that consumption of milk and dairy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 107 publications
1
55
0
Order By: Relevance
“…When combined with metformin, leucine and HMB improved insulin sensitivity by activating AMPK and SIRT1 [47]. Leucine content is high in dairy products and has been identified as a key component for lowering the risk for T2D [50]. …”
Section: Discussionmentioning
confidence: 99%
“…When combined with metformin, leucine and HMB improved insulin sensitivity by activating AMPK and SIRT1 [47]. Leucine content is high in dairy products and has been identified as a key component for lowering the risk for T2D [50]. …”
Section: Discussionmentioning
confidence: 99%
“…A discussion of these is beyond the scope of this article, but interested readers may explore topics not covered here in the following publications (45)(46)(47)(48)(49)(50).…”
Section: Other Considerationsmentioning
confidence: 99%
“…The use of whey protein in people with T2D has also garnered interest because it has been found to elicit a greater postprandial thermogenic response compared with casein or soy, greater satiety and suppression of subsequent food intake, as well as lower postprandial blood glucose concentrations by stimulating greater insulin secretion compared with other types of protein (48). Several prospective cohort studies also reported an inverse association between intakes of dairy protein and T2D risk, but additional research is necessary to better understand the mechanisms whereby dairy may be protective (49).…”
Section: Dietary Sources Of Proteinmentioning
confidence: 99%